Myocardial involvement in idiopathic inflammatory myopathies: a multi-center cross-sectional study in the CRDC-MYO Registry - Zhang, Lixi; Zhu, Huiyi; Yang, Pinting; Duan, Xinwang; Wei, Wei; Wu, Zhenbiao; Fang, Yongfei; Li, Qin; Liu, Shengyun; Shi, Xiaofei; Li, Hongbin; Wu, Chanyuan; et al. (Clinical rheumatology, 2021)
Objectives This study aimed to investigate the associated factors of myocardial involvements (MIs) in patients with idiopathic inflammatory myopathies (IIMs). Methods In this multi-center cross-sectional study, 1946 patients with IIMs were enrolled from Chinese Rheumatism Data Center-Myositis Registry (CRDC-MYO). A total of 108 (5.5%) patients were identified with MIs, including congestive heart failure (n = 67, 62.0%), and severe arrhythmias (n = 61, 56.5%). The other 1838 IIM patients without IMs were set as the control group. Clinical features were collected including age, gender, comorbidities, clinical symptoms, clinical signs of both IIMs and MIs, lab findings including myositis-specific antibodies (MSAs) and myositis-associated antibodies (MAAs), echocardiogram, and radiological exams. Multivariate logistic analysis was used to explore independent associated factors of MIs in patients with IIMs. Results Several independent associated factors were identified in multi-variate logistic regression, including positivity for anti-mitochondrial antibody-subtype 2 (AMA-M2) (OR 5.194, 95% CI 2.509–10.753, P < 0.001), elevation of creatine kinase (CK) (OR 2.611, 95% CI 1.312–5.198, P = 0.006), elevation of C-reactive protein (CRP) (OR 2.150, 95% CI 1.211–3.818, P = 0.001), and pulmonary hypertension (OR 4.165, 95% CI 1.765–9.882, P = 0.009). AMA-M2 and pulmonary hypertension were the most consistent associated factors in the polymyositis subgroup and the dermatomyositis/clinically amyopathic dermatomyositis subgroup. Conclusions MIs are rare but serious complication of IIMs could lead to congestive heart failure and severe arrhythmias. IIM patients with AMA-M2 positivity, elevation of CK and CRP, and pulmonary hypertension are more likely to develop MI complications. Key Points • This study investigated the independent associated factors for clinically significant myocardial involvements among idiopathic inflammatory myopathies in a large-scale, nation-wide multi-center cross-sectional study.